Apple Configurator 2 - Valencia, Samuel; Mitnick, Keith (Learn by video., 2016)
"Learn the basic concepts behind Apple Configurator and the types of devices it supports. Discover the new concept of Blueprints and working with MDM and DEP. For those users that have worked with Apple Configurator 1 before, you'll learn the steps to migrate your data to the current version. Learn to set up a clean Apple Configurator 2 workstation, discover what a Supervision Identity is, and create an organization. Customize the preferences and look and feel of Apple Configurator 2. Learn how to "prepare" an iOS device and export data. Also, discover options in the advanced menu. Learn to create a new Blueprint, create profiles and add Apps, and create prepare steps. This will allow you to have a template to use when you connect an unsupervised iOS device. In this video, learn about Supervising devices as you create Blueprints for devices that will allow for additional management features. You might find yourself using Apple Configurator 2 as an initial preparation method but using an MDM for continual management. In this lesson you'll see how to get the best of both worlds by having AC2 auto enroll your devices in an MDM solution. Apple's introduction of the Device Enrollment Program has allowed for much easier deployment of iOS devices. Apple Configurator 2 has the ability to work with DEP as well. Not everything can be done in the GUI (Graphical User Interface). More often than not, more advanced tools are available in UNIX. This video uncovers some of those tools and explains how to use them. Ever wanted to stop Photos from popping up every time you plug in a device? Or are you receiving an error you can't explain when trying to prepare? Learn how to make changes to AC2 under the hood that can help you be more efficient."--Resource description page.